How do you implicitly differentiate #-1=-y^2x+xy-ye^(xy) #?

Answer 1

# dy/dx={y(1-y-ye^(xy))}/{2xy+xye^(xy)+e^(xy)-x},#

OR

# dy/dx={y^3(xy-x-1)}/(xy+xy^2+x^2y^2-x^2y^3+1).#

To avoid #-ve#signs, let us rewrite the eqn. as,
#y^2x+ye^(xy)=xy+1.#

Diff.ing term-wise, using the usual Rules of Diffn., we get,

#{y^2d/dx(x)+xd/dx(y^2)}+{yd/dxe^(xy)+e^(xy)d/dx(y)}#
#=d/dx(xy)+0.#
#:. y^2(1)+x{d/dy(y^2)d/dx(y)}+ye^(xy)d/dx(xy)+e^(xy)dy/dx=d/dx(xy).#
#:. y^2+x{(2y)dy/dx}+ye^(xy){xdy/dx+yd/dx(x)}+e^(xy)dy/dx={xdy/dx+yd/dx(x)}.#
#:. y^2+2xydy/dx+ye^(xy){xdy/dx+y}+e^(xy)dy/dx=xdy/dx+y.#
#;. {2xy+xye^(xy)+e^(xy)-x}dy/dx=y-y^2-y^2e^(xy).#
#:. dy/dx={y(1-y-ye^(xy))}/{2xy+xye^(xy)+e^(xy)-x}.#
This Answer is fairly reasonable, but, if we replace #e^(xy)# from this, we can have better Answer as shown below :
#NR.=y{1-y-(xy+1-y^2x)}=y(1-y-xy-1+y^2x)=y(xy^2-xy-y)=y^2(xy-x-1).#
#DR.=2xy-x+x(xy+1-y^2x)+(xy+1-y^2x)/y,#
#=(2xy^2-xy+x^2y^2+xy-y^3x^2+xy+1-y^2x)/y#
#=(xy+xy^2+x^2y^2-x^2y^3+1)/y.#
#rArr dy/dx={y^3(xy-x-1)}/(xy+xy^2+x^2y^2-x^2y^3+1).#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To implicitly differentiate the equation -1=-y^2x+xy-ye^(xy):

  1. Differentiate each term with respect to x.
  2. Apply the product rule and chain rule where necessary.
  3. Solve for dy/dx.

Differentiating each term:

  1. For -1, the derivative is 0.
  2. For -y^2x, the derivative is -y^2 - 2yx(dy/dx).
  3. For xy, the derivative is y + x(dy/dx).
  4. For -ye^(xy), the derivative is -y^2e^(xy) - y^3x(dy/dx) - ye^(xy).

Combine the terms involving dy/dx: -2yx(dy/dx) + x(dy/dx) - y^3x(dy/dx) = -y^2 - y^2e^(xy)

Factor out dy/dx: (dy/dx)(-2yx + x - y^3x) = -y^2 - y^2e^(xy)

Solve for dy/dx: dy/dx = (-y^2 - y^2e^(xy)) / (-2yx + x - y^3x)

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7